A New perspective: How Pathogens Manipulate Phagocytosis? How Pathogens Manipulate Phagocytosis? - Li, Zhaolun; Gao, Yulu; Chen, Gang; Wang, Leili; Chu, Jiaqi; Han, Hongyu; Chen, Yuting; Zhou, Guang (Cellular and Molecular Biology, 2022)
The immune system is a complicated, closely regulated mechanism that evolved to keep people healthy from infectious pathogens. Phagocytosis is important for both innate and acquired immunity, which is a critical process for microbial pathogens and apoptotic cells to be consumed and eliminated. However, several pathogens have evolved different strategies to escape detection and killing by phagocytosis. Recently, with the increase in infectious diseases and antibiotic resistance, it is significant for people to have a deep understanding of immune evasion, which may become an opportunity to explore new treatments and vaccination. Additionally, researchers mostly study immune evasion of a single pathogen but rarely summarize pathogens from the perspective of immune mechanisms. Here, we present the current understanding of phagocytosis and give a brief discussion of how pathogens control phagocytosis at different stages.